Empregos de PORQUE no discurso oral - Paiva, Maria da Conceição de (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
In this analysis of the use of the Portuguese porque ("because") in oral speech, I argue that may of its occurences cannot be explained by means of logical -semantic descriptions. The data I examined revealed the following: I) porque appears in different kinds of constructions; 2) its function as an element of discourse organization is also varied: it may be linked to the previous, to the following and to both the previous and the following segments of the discourse.